Evaluating Training Programs According to model Kirkpatrick / field research in the Health Maysan Directorate . - عبد الزيدي, ناظم جواد; محمد, علي هاشم (Journal of Economics and Administrative Sciences, 2016)
This present paper aim at knowing  the process of evaluating the training program that could be applied  in Maysan Health office  for it significance and importance in field of management and vocational staff  preparations  of high  scientific experience in different fields of  Health.  The society of research includes staffs  working in Maysan Health Office  , of specialists ,  dentists, pharmacists, laboratories, nursing  and administrators. Their number is 100 employees, the researcher has designed questionnaire by depending on "Kirkpatrick"  for assessing  the training . The researcher has used   thorough survey and has entailed 90 questionnaire, the  researcher has used  analytic descriptive  method . For defining  levels of  hypotheses and coefficients of  the research , it has been employed  a number of  statistic means  into analyzing  and processing data  and information  by depending on  SPSS   represented into mathematic average , difference coefficient  to show  content of  coefficients  and Spearman coefficient  for measuring  the nature of  the relationship along with its degree  and comparing the results  to be analyzed.  The importance of the research  lie in presenting and knowing  nature of coefficients by depending on application  through applying  theoretical concepts  in practical field . The most important results , the researcher has reached to  lies into Maysan Health Office that the latter applies  and assess  the training on level of reaction, while , there  has been not suitable  assessment  directly or indirectly  on the level of behavior  and organize results  after finishing  the process of training.  Key words : Training Programs , Kirkpatrick model , Reaction , Learning , Behavior  , Results  .